Fitness center use and subsequent achievement of exercise goals. A prospective study on long-term fitness center members - Liv Riseth; Tom Ivar Lund Nilsen; Torunn Hatlen Nøst; Aslak Steinsbekk (BMC, 2022)
Abstract Background Knowledge on the relationship between fitness center use and long-term members' subsequent goal achievement is limited. Therefore, the aim was to investigate the prospective association between the use of fitness centers during 18 months and subsequent self-reported goal achievement among long-term members. Methods This was a registry- and survey-based longitudinal study of 2851 people who had been members at a Norwegian fitness center chain for more than two years. Fitness center use from December 2016 to June 2018 was obtained from registry data. Subsequent goal achievement was measured in a survey in June 2018, assessed by a 1-100 visual analogue scale, and a score between 0 and 50 was defined as low goal achievement. Results Visiting the fitness center frequently and regularly, and having frequent group activity bookings were associated with higher subsequent self-reported goal achievement. Participants with fewest visits (1-57 days) during 18 months were more likely to report low goal achievement than participants with most visits (118-543 days) (OR = 8.5; 95% CI 6.3-11.4). Fitness trainer bookings was not clearly associated with subsequent goal achievement. Conclusions Frequent and regular long-term fitness center use were associated with higher subsequent self-reported goal achievement.